Customers Satisfaction towards Life Insurance Claim Settlement in Nepal - Basaula, Damodar (Janapriya Journal of Interdisciplinary Studies, 2018)
Claim settlement has been like a mirror to each life insurance companies which public see the real face of their business. A company which fails to settle the claim, the satisfaction of customers would definitely distracts the business and discourage to continue or the repurchase of policy. The main purpose of the research paper is to examine the awareness and satisfaction of customers towards life insurance claim settlement in Nepal. Descriptive research designed has been employed in the study. Sample comprises 391 respondent agents for which stratified sampling were used. Primary data were obtained through questionnaire method specifically the five point likert scale. The data collected for the study were analyzed thought SPSS software and MS Excel too. The study revealed that majority of the respondents has neutral response on the satisfaction towards claim settlement. However they think that the claim settlement process speed would definitely help to increase life insurance business. The study revealed that government should focus on awareness of life insurance and make it mandatory for every citizen. Janapriya Journal of Interdisciplinary Studies, Vol. 6 (December 2017), page: 29-44